Proteome differences of dental stem cells between permanent and deciduous teeth by data-independent acquisition proteomics - Zhang Suping; Liu Yuqing; Dong Jin; Jiao Min; Gu Yongchun; Chen Liling; Yuan Na; Wang Jianrong; Yang Dezhao; Meng Fanwen (Open Life Sciences)
Dental pulp stem cells hold significant prospects for tooth regeneration and repair. However, a comprehensive understanding of the molecular differences between dental pulp stem cells (DPSC, from permanent teeth) and stem cells from human exfoliated deciduous teeth (SHED, from deciduous teeth) remains elusive, which is crucial for optimizing their therapeutic potential. To address this gap, we employed a novel data-independent acquisition (DIA) proteomics approach to compare the protein expression profiles of DPSC and SHED. Based on nano-LC-MS/MS DIA proteomics, we identified over 7,000 proteins in both cell types. By comparing their expression levels, 209 differentially expressed proteins were identified. Subsequent Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses, along with protein–protein interaction network construction, revealed significant metabolic differences and key regulatory nodes. DPSC exhibited significantly higher expression of proteins belonging to the NDUFB family, SMARC family, RPTOR and TLR3. These proteins are known to be involved in critical cellular processes such as mitochondrial energy metabolism, mTOR-related autophagy pathway, and innate immune response. Conversely, SHED displayed elevated expression of AKR1B family, which participated in glycerolipid metabolism and adipogenic differentiation, PRKG1, MGLL and UQCRB proteins associated with thermogenesis. These findings highlight the specific proteomic landscape of DPSC and SHED, suggesting their distinct biological roles and potential applications.